Network fault location based on bipartite graphs for communication and information networks - Limin CUI; Qingsu HE; Junsheng WANG; Xin SHI (Dianxin kexue)
The current State Grid communication and information networks rely on two separate network management systems.Such management structure brings challenges to network fault location,which calls for joint network fault analyze method. Grasping the transmission correlation of network nodes, a joint network fault location mechanism based on bipartite graph model was proposed.Firstly,network nodes were clustered into multiple sub-domains based on their fault correlation.Then,the bipartite graph fault correlation model was established for each sub-domain.Finally,the target sorting method was applied to locate network faults in every sub-domain simultaneously.Simulation experiments show that this method can locate network faults with high accuracy.